2021
DOI: 10.3389/fmars.2021.758651
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Marine Heatwaves on Algal Structure and Carbon Sequestration in Conjunction With Ocean Warming and Acidification

Abstract: As the ocean warms, the frequency, duration, intensity, and range of marine heatwaves (MHWs) increase. MHWs are becoming a severe challenge for marine ecosystems. However, our understanding in regard to their impacts on algal structure and carbon sequestration is still deficient or fragmentary, particularly when combined with ocean warming and acidification. In this paper, we reviewed the impacts of MHWs individually and combined with ocean warming and acidification on regime shift in algal community and carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 102 publications
(121 reference statements)
0
22
0
Order By: Relevance
“…Numerous studies have also reported that marine heatwaves have triggered massive HABs in many places globally [18,[53][54][55][56][57][58][59][60][61]. However, the process and mechanism, namely, how marine heatwaves trigger HABs, has not been accurately understood.…”
Section: Relationship Of Algal Outbreaks To Marine Heatwavesmentioning
confidence: 99%
“…Numerous studies have also reported that marine heatwaves have triggered massive HABs in many places globally [18,[53][54][55][56][57][58][59][60][61]. However, the process and mechanism, namely, how marine heatwaves trigger HABs, has not been accurately understood.…”
Section: Relationship Of Algal Outbreaks To Marine Heatwavesmentioning
confidence: 99%
“…Fluctuating ocean conditions due to anthropogenic climate change can affect individual species, community structure, and ecosystem function. Extreme climatic events have altered a range of ecosystem processes, including increasing direct mortality by exceeding species’ physiological thresholds 1 , altering biogeochemical cycles 2 , creating phenological mismatches with food resources 3 , and shifts in species ranges 4 , 5 . Changes in these processes have led to rapid reorganization of marine communities 6 , 7 , loss of ecosystem function, and increasing exploitation of certain fish species from human harvest 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, global models predict a positive effect of marine heatwaves on phytoplankton biomass in nutrient-replete conditions and the opposite in nutrient-poor conditions, with drastic phytoplankton biomass reductions in tropical areas (Hayashida et al, 2020;Sen Gupta et al, 2020). Marine heatwaves could also induce a shift in the phytoplankton community toward smaller cells, with consequences for the ecosystem functioning and carbon sequestration (Gao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%